Congenital pulmonary airway malformation - A histomorphological spectrum of 15 cases: A 5-year study from a tertiary care center - Kanika Gupta; Vishal Singh; Shramana Mandal; Varuna Mallya; Meeta Singh; Nita Khurana; Y K Sarin (Wolters Kluwer Medknow Publications, 2021)
Objective: Congenital pulmonary airway malformation (CPAM) is a rare developmental lung disease. The aim of this study is to analyze the histomorphological spectrum of CPAM in a series of 15 cases. Materials and Methods: A retrospective descriptive study of 15 cases of CPAM was carried out from 2013 to 2018 in our hospital, and cases were classified based on the Stocker's classification. Results: The age ranged from 4 days to 9 years (66.6% were infants). The left lung was most commonly involved (66.6%). The most common lobe was the left upper lobe (60%), followed by right lower lobe (20%). Grossly, cysts measured 0.2-5 cm, filled with mainly serous fluid with few having hemorrhagic and brownish mucoid secretions. On microscopy, single to multiple noncommunicating cysts of size 0.2-5 cm were seen, lined by ciliated columnar epithelium (60%), pseudostratified ciliated columnar epithelium (26.7%), mucin-secreting columnar epithelium (6.7%), and flattened epithelium (6.7%). Few cases showed smooth muscle (20%) and cartilage (13.3%) in the cyst wall. Chronic inflammation (73.3%) with dense histiocytic infiltrate (13.3%) was also seen. Emphysematous changes were also observed (13.3%). Cytomegalovirus inclusions (6.7%), zygomycete fungus (6.7%), and red hepatization (6.7%) were observed. The most common type was type II (60%), followed by type I (33.3%) and type IV (6.7%). Conclusion: Type II was the most common variant in this study. A careful observation should be done to look for fungal hyphae or viral inclusions.